The Effect of Muslim Religiosity on Youth Delinquency. (September 2021) - Sahin, Ismail; Unlu, Ali
Conceptualizing religiosity as a multidimensional construct, this study aimed to investigate the influence of religiosity on youth delinquency. Three dimensions of religiosity—belief about religion, religious practice, and religious social environment—were examined as predictors of delinquency. The survey data collected in 2010 by the Governance of Istanbul, Istanbul Department of Education, and Istanbul Police Department were used. Participants were high school students ( n = 31, 272) between 14 and 18 years. Structural equation modeling was used for statistical analysis and hypothesis testing. The study found a relationship between the dimensions of religiosity and delinquency. While dimensions of beliefs about the religion and religious social environment correlate negatively with delinquency, the dimension of religious practices correlates positively with it. Belief about one's religion was found to be the strongest of the three dimensions. The findings suggested that religion has the potential to reduce the risk of delinquency among youth. Implications for future research and policy makers were also discussed.